2004
DOI: 10.1253/circj.68.483
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Multivessel Coronary Vasospasm by Detecting Postischemic Regional Left Ventricular Delayed Relaxation on Echocardiography Using Color Kinesis

Abstract: pisodes of coronary vasospasm are characterized by transient myocardial ischemia resulting from the temporary obstruction to coronary flow followed by reperfusion. Regional left ventricular (LV) diastolic dysfunction or delayed relaxation with prolonged isovolumic relaxation time may follow the transient, severe myocardial ischemia associated with coronary vasospasm and persist well beyond the recovery of the regional systolic dysfunction. 1-3 Color kinesis (CK) (Philips Medical Systems) is a new technique bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The CK-diastolic index was defined as the LV segmental filling fraction during the first 30% of the diastolic filling time (LV segmental cavity area expansion during the first 30% of diastole, divided by the segmental end-diastolic LV cavity area expansion, expressed as a percentage). [12][13][14] The mean CK-diastolic indexes in 40 age-matched control subjects were 71±6, 72±7 and 75±7% in the territory of AS, LAT and INF, respectively. Intraobserver variability of the CK-diastolic index was 6.5±3.4% (n=18).…”
Section: Ck Studymentioning
confidence: 96%
See 3 more Smart Citations
“…The CK-diastolic index was defined as the LV segmental filling fraction during the first 30% of the diastolic filling time (LV segmental cavity area expansion during the first 30% of diastole, divided by the segmental end-diastolic LV cavity area expansion, expressed as a percentage). [12][13][14] The mean CK-diastolic indexes in 40 age-matched control subjects were 71±6, 72±7 and 75±7% in the territory of AS, LAT and INF, respectively. Intraobserver variability of the CK-diastolic index was 6.5±3.4% (n=18).…”
Section: Ck Studymentioning
confidence: 96%
“…A custom software program was used to extract endocardial expansion for myocardial segments in the LV midpapillary shortaxis view, as reported previously. [12][13][14]16,17 The timing of color encoding was set to begin at the first frame in which outward endocardial motion was noted, and its duration was set to its maximal value (33 ms × 19 frames). The sites of regional LV diastolic wall motion or regions of interest were set on the basis of standard segmentation models corresponding to the 3 major coronary perfusion territories assigned as follows (Fig 1) 18 : (i) the anterior and anteroseptal segments (AS) to the left anterior descending coronary artery (LAD); (ii) the anterolateral and posterolateral free wall segments (LAT) to the left circumflex branch (LCX) or the diagonal branches originated from LAD; and (iii) the posteroseptal and inferior segments (INF) usually to the right coronary artery (RCA).…”
Section: Ck Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Ishii et al reported that delayed relaxation or delayed contraction is observed in patients with vasospastic angina for several weeks after attack of spasm on color kinesis. 24, 25 The ischemic memory in myocardial contraction is thought to remain for hours or days or weeks. 5,26,27 This ischemic memory is explained by the delay of metabolic stunning even after blood flow restoration.…”
Section: Tpsc Vs Tpsc Ratiomentioning
confidence: 99%